Localization of auroral Langmuir turbulence in thin layers. Issue 6 (6th June 2013) - Akbari, H.; Semeter, J. L.; Nicolls, M. J.; Broughton, M.; LaBelle, J. W.
Abstract : [1] The recently discovered coherent echoes in the Poker Flat Incoherent Scatter Radar data with flat ion‐line spectrum and simultaneous double‐peaked plasma‐line spectrum in the lower ionospheric F region are investigated in greater detail. High‐range resolution measurements reveal that the turbulence is sometimes manifested as two concurrent layers separated by about 50 km. The turbulence layers appear at regions of zero electron density gradient, supporting the interpretation that propagation effects play an important role in limiting the waves' amplitude. Although Langmuir intensity is limited by propagation effects outside of the layers, it reaches to nonlinear regime inside the layers, giving rise to the observed range and spectral morphologies. Furthermore, the radar measurements of the electrostatic waves appear to be correlated in space and time with natural auroral electromagnetic emissions, supporting the previous theory that "MF‐bursts" are produced by linear conversion of Langmuir waves produced by soft electron precipitation (~few hundred electronvolts) on the topside F region. The results presented in this report suggest that the observed Langmuir turbulence and MF‐burst are both manifestations of the same process. Key Points: Langmuir turbulence and MF‐burst are both manifestations of the same process. Convective saturation play a role in saturating the Langmuir intensity.